Sarcoma of the Uterus. Guideline of the DGGG (S2k-Level, AWMF Registry No. 015/074, August 2015) - Denschlag, D.; Thiel, F. C.; Ackermann, S.; Harter, P.; Juhasz-Boess, I.; Mallmann, P.; Strauss, H. -G.; Ullrich, U.; Horn, L. -C.; Schmidt, D.; Vordermark, D.; Vogl, T.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Purpose: Official guideline published and coordinated by the German Society of Gynecology and Obstetrics (DGGG). Due to their rarity and their heterogeneous histopathology uterine sarcomas remain challenging tumors to manage and need a multidisciplinary approach. To our knowledge so far there is no evidence-based guideline on the appropiate management of these heterogeneous tumors. Methods: This S2k-guideline is the work of an representative committee of experts from a variety of different professions who were commissioned by the DGGG to carry out a systematic literature review of uterine sarcoma. Members of the participating scientific societies developed a structured consensus in a formal procedure. Recommendations: 1. The incidence and histopathologic classification of uterine sarcoma. 2. The clinical manifestations, diagnosis and staging of uterine sarcoma. 3. The management of leiomyosarcoma. 4. The management of endometrial stromal sarcoma and undifferentiated uterine sarcoma. 5. The management of adenosarcoma as well as carcinosarcomas. 6. The management of morcellated uterine sarcoma.
EVALuna2:17600